Next generation of ICeGaNⓇ for superior no load and light load performance - Kalparupa Mukherjee; Jin Zhang; Kaspars Ledins; Carlos Toyos Bada; Nirmana Perera; Loizos Efthymiou; Sheung Wai Fung; Martin Arnold; Giorgia Longobardi; Florin Udrea (Power Electronic Devices and Components)
The ICeGaNⓇ technology aims at enabling widespread adoption of GaN HEMTs in power applications through a monolithic solution that offers an increased VGS(th) (2.9 V) and a wide ON-state gate driving range of 9 V to 20 V. This makes it compatible with industry standard Si gate-driver ICs and controller ICs. The first ICeGaN product series (H1) introduced the integrated circuit interface to the gate of a standard enhancement mode 650 V p-GaN HEMT, offering superior flexibility, reliability, and protection features. The interface regulates the internal gate of the p-GaN HEMT to stay within a safe range across different temperatures and includes a Miller clamp transistor which prevents spurious turn-ON during high dV/dt events by swiftly grounding the internal pGaN gate when the external gate is turned OFF. In ICeGaN devices, a Vdd supply powers the IC interface, and it has a finite contribution to the device power consumption dependent on operating conditions. The second series of ICeGaN products (H2) comprising of 55, 130 and 240 mΩ power devices, advances the ICeGaN concept with an intelligent fully integrated NL3 circuit which aims at particularly minimizing the power losses under no-load and light-load conditions. When the external gate is in OFF state, the current consumption of the Vdd pin (Idd) is reduced to near-zero (typical 70 µA) in H2 devices. In the gate ON state, the Idd is reduced by 40 % (typical 1 mA) compared to H1 (typical 1.7 mA). This work presents the characterization and comparison of the 55 mΩ devices from the H2 and H1 ICeGaN product series.